2016
DOI: 10.1120/jacmp.v17i2.5980
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of volumetric‐modulated arc therapy for malignant pleural mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is an extremely difficult disease to treat. This pilot study investigates the feasibility of using volumetric‐modulated arc therapy (VMAT) for malignant pleural mesothelioma (MPM), and compares VMAT to static field intensity‐modulated radiotherapy (IMRT) for five patients. To identify the best treatment technique for MPM, in five patients, we made a representative comparative analysis of two kinds of techniques for radiation therapy planning: IMRT and VMAT. The plans were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Limited published benchmark data of treatment times for RT for MPM exist. Two prior publications report treatment delivery times of 5.0-5.4 min for VMAT for MPM, but direct comparison is limited in that the treatment volumes in those studies encompassed the entire hemithorax, a much larger treatment volume than in our study, which could independently lengthen treatment time (7,23). The beamon and treatment times observed compare favorably with those of patients treated for breast cancer (2.0±0.3 and 4.4±0.4 min, respectively) and gynecologic cancers (2.9±0.4 and 3.6±0.4 min, respectively) on Halcyon TM , while again recognizing the limitation of the differences in disease sites, setup details, and treatment volumes (17,18).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Limited published benchmark data of treatment times for RT for MPM exist. Two prior publications report treatment delivery times of 5.0-5.4 min for VMAT for MPM, but direct comparison is limited in that the treatment volumes in those studies encompassed the entire hemithorax, a much larger treatment volume than in our study, which could independently lengthen treatment time (7,23). The beamon and treatment times observed compare favorably with those of patients treated for breast cancer (2.0±0.3 and 4.4±0.4 min, respectively) and gynecologic cancers (2.9±0.4 and 3.6±0.4 min, respectively) on Halcyon TM , while again recognizing the limitation of the differences in disease sites, setup details, and treatment volumes (17,18).…”
Section: Discussionmentioning
confidence: 75%
“…Volumetric-modulated arc therapy (VMAT), is a form of IMRT in which RT is delivered in continuous, dynamic arcs. While published reports of the use of VMAT in MPM are limited, it has been shown that VMAT can significantly improve MPM treatment homogeneity and conformity indices and shorten treatment delivery times as compared to fixed-field IMRT (7), with reasonable toxicity (8).…”
Section: Introductionmentioning
confidence: 99%
“…And IMRT/VMAT/HT therapy are being used more commonly now than historically ( 8 ). For instance, several studies have shown that conventional static IMRT achieves better dose coverage and improved local control compared with 3DCRT ( 6 - 13 ) for MPM, while other studies have demonstrated that VMAT allows for even better dose conformality in a shorter delivery time compared with static IMRT, sparing potential organs at risk (OARs) during MPM radiotherapy ( 14 - 16 ). Moreover, several studies exploring the feasibility of prescription dose escalation using HT and VMAT have also been reported ( 17 - 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The IMPRINT and SMART trials are examples of a possible and safe therapeutic benefit of RT within a multimodal approach 34 . However, owing to a lack of large clinical studies with definitive results, the role of RT largely remains within the settings of clinical trials and palliation 8 , 19 , 35 .…”
Section: Radiation Therapymentioning
confidence: 99%